Trends and approaches to reorganization of urban environment - Sedin, Volodymyr; Kovalov, Viacheslav; Kravchunovska, Tetiana; Nechepurenko, Daria (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article describes the standards of urban environment reorganization, which are oriented to the effective use of land resources and the load distribution for urban transport infrastructure, a high degree of functional diversity. The authors have analyzed the approaches and trends of the urban environment transformation, based on the concept of the compact cities formation. The authors determined specific features of the urban industrial environment transformation different types depending on the degree and direction of the objects modification. In the conditions of land plots shortage, redevelopment projects provide an opportunity to renew the urban environment, to solve transport problems, and to find the potential for building new objects.